Geometrical tolerance transfer for sheet metal forming processes - Wang, Rui (2008)
As an essential link between sheet metal design and manufacturing, process planning generates a sequenced set of instructions to manufacture parts. However, according to a literature survey in this thesis, the tolerance transfer issue in sheet metal forming are insufficiently addressed: machining errors and their causes are not presented comprehensively as the sources of final error; only size dimensional tolerances are discussed in detail; computer aided tolerancing for parts formed by multiple operations jointly such as bending, punching, and blanking, is seldom studied; statistical tolerancing are utilized only for sheet metal assembly issues or size dimensional tolerances, not geometric tolerances. Therefore, according to these problem unaddressed, the presented research is motivated to explore and to propose systematically three dimensional geometrical tolerance transfer approaches for sheet metal part forming. The here proposed models are suitable for worse case or statistical analysis (using the Monte-Carlo methods). First, an integrated CAD/CAPP system based on feature evolvement, associative features, and data association mechanism, is outlined. Then, a mathematical model of geometric tolerance transfer is proposed. For Monte Carlo simulations, the distribution of final errors may not closely follow the normal distributions. Finally, a machining error-correlated cost model is presented and applied to tolerance synthesis using a case of parallelism tolerance. Angular errors are demonstrated to affect final errors vastly. This tolerance transfer method is applied on parts formed by bending (parallel and non-parallel) and punching operations jointly. It can be applied on all bending-like and cutting operations easily and extended to other sheet metal forming operations. The research work is a solid basis for future work in this area.